A Comprehensive Framework of Design Thinking Approach in Knowledge Management: A Review in Academic Context - Mostofa, Sk Mamun; Othman, Roslina; Mukherjee, Debarshi; Hasan, Khandakar Kamrul (Journal of Education Culture and Society, 2020)
Aim of research. Design thinking (DT) is an essential context for knowledge management (KM), as it promotes the link between KM initiatives and an organization's strategic goals and objectives. This article analyzes the DT process in terms of its capability to create KM. The detailed analysis on the aspect of the working mechanism of DT – how KM is represented and created in the process. This article examines the DT procedure in terms of its ability to generate design knowledge. In this regard, the main purpose of this paper is to review the approaches to KM applied to DT and to suggest directions for how such a supervisory system could evolve.Methodology. This study is thematic in its nature and it was prepared on the basis of secondary data and also based on an inclusive review of the literature and similarly computation of secondary information. To formulate this paper the researchers used books, earlier published articles, conference papers, and numerous research reports.Results and conclusions. This article concludes by proposing an intuitive model for DT and KM. KM for its successful application in higher learning institutions in the areas of course design institutional strategy formation and faculty resource sharing.